2019
DOI: 10.1128/aac.00379-19
|View full text |Cite
|
Sign up to set email alerts
|

Phage Therapy of Pneumonia Is Not Associated with an Overstimulation of the Inflammatory Response Compared to Antibiotic Treatment in Mice

Abstract: Supported by years of clinical use in some countries and more recently by literature on experimental models, as well as its compassionate use in Europe and in the United States, bacteriophage (phage) therapy is providing a solution for difficult-to-treat bacterial infections. However, studies of the impact of such treatments on the host remain scarce. Murine acute pneumonia initiated by intranasal instillation of two pathogenic strains of Escherichia coli (536 and LM33) was treated by two specific bacteriophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 43 publications
2
57
1
3
Order By: Relevance
“…Pincus et al ( 2015 ) showed that a staphylococcal phage induces interferon gamma in primary human keratinocyte cultures but not in blood MNC. Likewise, E. coli phages elicited marked production of IFN gamma and IL-12 by lung cells but not MNC (Dufour et al, 2019 ).…”
Section: Phages May Induce Production Of Cytokines and Other Biologicmentioning
confidence: 99%
“…Pincus et al ( 2015 ) showed that a staphylococcal phage induces interferon gamma in primary human keratinocyte cultures but not in blood MNC. Likewise, E. coli phages elicited marked production of IFN gamma and IL-12 by lung cells but not MNC (Dufour et al, 2019 ).…”
Section: Phages May Induce Production Of Cytokines and Other Biologicmentioning
confidence: 99%
“…The intranasal administration of 536_P1 (but not LM33-P1) coliphage in mice with experimental pneumonia caused an increase in lung antiviral cytokines and chemokines. Neither phage evoked changes in blood cytokine/chemokine levels, which also suggests that phage effects on the immune system may have various manifestations in different compartments of the body [16]. Phage ability to mediate tissue-specific activity is confirmed by Pincus et al [17], where staphylococcal phage did not induce proinflammatory cytokines in human peripheral blood mononuclear cells but may have induced IFN-γ in human keratinocytes.…”
mentioning
confidence: 99%
“…Phages also do not induce significant amounts of inflammation. Dufour et al (2019) found that phages could elicit cytokine production above baseline, but this was localized, phage dependent, and had no observable clinical consequences. Other work has shown that when uninfected mice were given inhalational or intraperitoneal phages, no appreciable levels of either TNF-α or MIP-2 were observed in the lungs ( Carmody et al, 2010 ).…”
Section: Toxicity and Immune Responsementioning
confidence: 99%